No adiabaticidad en moléculas y el efecto Jahn-Teller - Castro, J.J.; Yépez, E.; Soto, J.R. (Revista Mexicana de Física E, 2004)
In studying the electron properties in molecules and solids, the Born-Oppenheimer approximation is the most commonly used. Going beyond this approximation implies that the motion of the electrons and nuclei is coupled, given rise to what is known as vibronic states, manifesting with new chemical and physical properties. In this work we present a brief review of one of the most striking manifestations of vibronic coupling in molecules and clusters, the Jahn-Teller and pseudo Jahn-Teller effect. We discussed the conditions for the failure of the adiabatic approximation and the applicability of a perturbative approach to find the vibronic states. We also present the use of group theory techniques to calculate the vibronic coupling. As an example, we present a Jahn-Teller analysis for the CuO_6 cluster in regular and deformed octahedral arrays, O_h and D_4h symmetries respectively.